The shape and shaping of the Book of Psalms : the current state of scholarship - DeClaissé-Walford, Nancy L., 1954- (Ancient Israel and its literature, 2014)
"This volume explores questions of communities of faith, of collections of psalms, of theological viewpoints, of sovereignty, and, most of all, of the shape and shaping of, arguably, the most beloved book of the Old Testament"--